A suppressor of an RNA polymerase II mutation of Saccharomyces cerevisiae encodes a subunit common to RNA polymerases I, II, and III. - Archambault, J (1990)
RNA polymerase II (RNAPII) is a complex multisubunit enzyme responsible for the synthesis of pre-mRNA in eucaryotes. The enzyme is made of two large subunits associated with at least eight smaller polypeptides, some of which are common to all three RNA polymerase species. We have initiated a genetic analysis of RNAPII by introducing mutations in RPO21, the gene encoding the largest subunit of RNAPII in Saccharomyces cerevisiae. We have used a yeast genomic library to isolate plasmids that can suppress a temperature-sensitive mutation in RPO21 (rpo21-4), with the goal of identifying gene products that interact with the largest subunit of RNAPII. We found that increased expression of wild-type RPO26, a single-copy, essential gene encoding a 155-amino-acid subunit common to RNAPI, RNAPII, and RNAPIII, suppressed the rpo21-4 temperature-sensitive mutation. Mutations were constructed in vitro that resulted in single amino acid changes in the carboxy-terminal portion of the RPO26 gene product. One temperature-sensitive mutation, as well as some mutations that did not by themselves generate a phenotype, were lethal in combination with rpo21-4. These results support the idea that the RPO26 and RPO21 gene products interact.